Clinical testing for overactive bladder - Nitti, Victor (Canadian Urological Association Journal, 2013)
While the diagnosis of overactive bladder (OAB) is made clinically, simple office testing (e.g., urinalysis and culture, assessment of post-void residual urine) should be part of the work-up of all patients with these symptoms. There are certain situations in which testing should be undertaken before initiating treatment or for monitoring response. Supplemental testing should be considered in cases where routine evaluation raises the suspicion of a problem or condition that either needs further evaluation or may predispose the patient to failure of therapy. Further testing may also be considered for patients who are refractory to treatment and those with significant neurological disease. Depending on the particular case, supplemental testing may include comprehensive urodynamic testing, endoscopic evaluation of the lower urinary tract, imaging of the upper urinary tract, neurologic evaluation or spine imaging.